2012
DOI: 10.1021/jf300787b
|View full text |Cite
|
Sign up to set email alerts
|

Hemicelluloses Prior to Aspen Chemithermomechanical Pulping: Pre-Extraction, Separation, and Characterization

Abstract: A portion of hemicelluloses and acetic acid can be pre-extracted with dilute sulfuric acid prior to the aspen chemithermomechanical pulp process. The streams collected from the second press-impregnation stage after acid pre-extraction contain a significant amount of acid pre-extracted hemicelluloses. Most of the total sugars obtained from the pressate were xylan, in which xylan was further hydrolyzed to sugar monomers under the acid pre-extraction condition. To fully understand the characteristics of hemicellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The removal of lignin and hemicelluloses could be responsible for the energy reduction for refining, resulting in more loose, collapsible, and easier separable fibers. A similar behavior was observed by Liu et al (2012) in the CTMPs after the HT of Populus tremuloides Michx.…”
Section: Ctmp Pulpingsupporting
confidence: 82%
See 1 more Smart Citation
“…The removal of lignin and hemicelluloses could be responsible for the energy reduction for refining, resulting in more loose, collapsible, and easier separable fibers. A similar behavior was observed by Liu et al (2012) in the CTMPs after the HT of Populus tremuloides Michx.…”
Section: Ctmp Pulpingsupporting
confidence: 82%
“…The tear index was slightly higher in the pulps from HT chips. Liu et al (2012) found that the HT P. tremuloides pulps have a similar tear index than the untreated control pulps. According to Spiegelberg (1966), the removal of hemicelluloses decrease the strength properties of the fibers by the inhibition of the internal stress distribution, replacing the flexible hemicellulose-cellulose bond by a more rigid cellulose-cellulose bond.…”
Section: Ctmp Pulpingmentioning
confidence: 84%
“…2,3 Hemicellulose can be extracted from biomass via hydrolysis prior to pulping or cellulosic ethanol production. 4 Steam or hot water hydrolysis is commercially used in pulp production from hardwood species. 1,5 It is therefore understood that hemicellulose can be available at a large quantity for use.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, prehydrolysis liquor (PHL) is identied as a potential feedstock for OS production and receives great attention due to its contribution to the industrial biorenery. [5][6][7][8] However, PHL also contains various non-saccharide compounds (NSC) that are released during the prehydrolysis step. NSC includes wood resins, water soluble aromatic compounds from lignin depolymerization, 9,10 organic acids and furans from carbohydrate degradation.…”
Section: Introductionmentioning
confidence: 99%